Public perception of drinking water from private water supplies: focus group analyses - McEwen Scott A; Majowicz Shannon E; Doré Kathryn; Dewey Catherine E; Jones Andria Q; Waltner-Toews David; Henson Spencer J; Mathews Eric (BMC, 2005)
Abstract Background Over four million Canadians receive their drinking water from private water supplies, and numerous studies report that these supplies often exceed the minimal acceptable standards for contamination. Canadians in rural areas test their water intermittently, if at all, and treatment of water from private supplies is not common. Understanding the perceptions of drinking water among residents served by private systems will enable public health professionals to better target education and outreach activities, and to address the needs and concerns of residents in their jurisdictions. The purpose of this study was to explore the drinking water perceptions and self-described behaviours and needs of participants served by private water systems in the City of Hamilton, Ontario (Canada). Methods In September 2003, three focus group discussions were conducted; two with men and women aged 36-65 years, and one with men and women 20-35 years of age. Results Overall, participants had positive perceptions of their private water supplies, particularly in the older age group. Concerns included bacterial and chemical contamination from agricultural sources. Testing of water from private supplies was minimal and was done less frequently than recommended by the provincial government. Barriers to water testing included the inconvenience of the testing process, acceptable test results in the past, resident complacency and lack of knowledge. The younger participants greatly emphasized their need for more information on private water supplies. Participants from all groups wanted more information on water testing, and various media for information dissemination were discussed. Conclusion While most participants were confident in the safety of their private water supply, the factual basis for these opinions is uncertain. Improved dissemination of information pertaining to private water supplies in this population is needed. Observed differences in the concerns expressed by users of different water systems and age groups may suggest the need for targeted public education strategies. These focus groups provided significant insight into the public perception of private water supplies and the need for public health outreach activities; however, to obtain a more representative understanding of the perceptions in this population, it is important that a larger scale investigation be performed.